No to sedentarianism, yes to health: contributions of school physical education and sports - Silva Alves, Ubiratan (O Mundo da Saúde, 2007)
One of the great problems faced by people in the world relates to the sedentarianism. Obesity, cardiac troubles, diabetes and many other diseases associate with this, and their emergence have very worrying rates mainly in young populations in school age. Technology seems to aggravate even more this situation. However, the regular practice of physical activities, with orientations, adequate clothes and spaces, associated to a healthful feeding can contribute to reduce these rates. Due to the risks faced by urban populations regarding violence, school still seems to be one of the few if not the only refuge and place for these practices nowadays. These practices in school deserve to be more planned so that the biggest number of pupils can benefit from them. The proposals of school practices must go beyond a sport specialization and try to enter the field of newness in the sense of presenting other activities: not only sports but also dancing, gymnastics, rhythmic activities among others. Even then, when having sports as its focus, Physical Education in the school must extend the gamma of practice possibilities for this way will we possibly to minimize this so painful picture for health.